Index-based weather insurance for perennial crops: A case study on insurance supply and demand for cocoa farmers in Ghana. (December 2020) - Afriyie-Kraft, Lydia; Zabel, Astrid; Damnyag, Lawrence
Highlights: More than 90% of respondents are interested in index insurance. Tenure, access to extension service and the cocoa farm's age are determinants of interest in index insurance. Supply-side stakeholders identify various shortcomings hampering index insurance implementation. A well-planned insurance policy, improvements in data quality and the diversity of sources could help address basis risks. Abstract: Adaptation to climate change is crucial for many farming households around the world. Due to path dependencies, perennial crop farmers often face a confined set of adaptation options. This paper explores the potential for index-based weather insurance for cocoa as an example of a perennial crop. The paper presents empirical findings on determinants of interest in index insurance based on a sample of 313 cocoa farming households in Ghana. Further, results of key informant interviews with representatives relevant for the planning and implementation of index insurance are presented. A key finding on the demand side is that more than 90% of the sampled cocoa farmers are interested in index insurance. The main determinants for interest were ownership of the cocoa farm, access to extension services, and age of the cocoa farm. For the supply side, main findings are that while stakeholders showed a general appreciation of the conceptual benefits of index insurance, a plethora of disadvantages and obstacles relating to insurance implementation were mentioned ranging from insufficient data and infrastructure, over low profitability, to wrong perceptions of insurance among farmers. The paper concludes that structural changes to the cocoa economy are necessary to address these impediments in the long run.